Dual mobility versus conventional total hip arthroplasty in femoral neck fractures (DISTINCT): protocol for a registry-nested, open-label, cluster-randomised crossover trial. Issue 9 (21st September 2022) - Farey, John E; Hooper, Tamara; Alland, Tania; Naylor, Justine M; Kelly, Thu-Lan; Lorimer, Michelle; Lewin, Adriane M; Rogers, Margaret; Law, Chi Kin; Close, Jacqueline; Graves, Steven E; de Steiger, Richard S; et al.
Abstract : Introduction: Hip fractures treated with total hip arthroplasty (THA) are at high risk of prosthesis instability, and dislocation is the most common indication for revision surgery. This study aims to determine whether dual mobility THA implants reduce the risk of dislocation compared with conventional THA in patients with hip fracture suitable to be treated with THA. Methods and analysis: This is a cluster-randomised, crossover, open-label trial nested within the Australian Orthopaedic Association National Joint Replacement Registry (AOANJRR). The clusters will comprise hospitals that perform at least 12 THAs for hip fracture per annum. All adults age ≥50 years who meet the Australian and New Zealand Hip Fracture Registry guidelines for THA will be included. The intervention will be dual mobility THA and the comparator will be conventional THA. Each hospital will be allocated to two consecutive periods, one of dual mobility THA and the other of conventional THA in random order, aiming for an average of 16 patients eligible for the primary analysis per group (32 total per site), allowing different recruitment totals between sites. Data will be collected through the AOANJRR and linked with patient-level discharge data acquired through government agencies. The primary outcome is dislocation within 1 year. Secondary outcomes include revision surgery for dislocation and all-cause, complications and mortality at 1, 2 and 5 years. If dual mobility THA is found to be superior, a cost-effectiveness analysis will be conducted. The study will aim to recruit 1536 patients from at least 48 hospitals over 3 years. Ethics and dissemination: Ethics approval has been granted (Sydney Local Health District - Royal Prince Alfred Hospital Zone (approval X20-0162 and 2020/ETH00680) and site-specific approvals). Participant recruitment is via an opt-out consent process as both treatments are considered accepted, standard practice. The trial is endorsed by the Australia and New Zealand Musculoskeletal Clinical Trials Network. Trial registration number: ACTRN12621000069853.